Metode Komunikatif dengan Role Play Berbasis Gender dalam Pembelajaran Kalām - Furaida Ayu Musyrifa; Khabibi Muhammad Luthfi (Alsina : Journal of Arabic Studies, 2021)
The purpose of this paper is to examine the relationship between communicative methods and role play in a philosophical-methodological manner, and to apply role play in gender-based kalām learning. This is motivated by the uncertainty of the position and the theoretical foundation of the communicative method and role play in the structure of the Arabic learning methodology. In addition, so far the study of methodology has been limited to structural-procedural, has not touched the meaning-contextual aspect so that it cannot include certain values, such as gender justice, even though behind Arabic there is a patriarchal culture of the Arab nation which should be minimized. With a philosophical-methodological approach based on library data and discourse analysis, it is found that role playing is a technique of the communicative method. When role play is applied in gender-based kalām learning, the concept of elements at the philosophical-theoretical and implementative-technical levels of the communicative method must be reconstructed with an anthropolinguistic approach using critical discourse analysis from poststructural equipped with additional components, such as text, themes, role functions, how to form groups, convey educators, and linguistics, which are based on the discourse of gender justice.